2021
DOI: 10.1002/advs.202002889
|View full text |Cite
|
Sign up to set email alerts
|

Pb Single Atoms Enable Unprecedented Catalytic Behavior for the Combustion of Energetic Materials

Abstract: Manipulating the thermal decomposition behavior of energetic materials is the key to further pushing the combustion performance of solid rocket propellants. Herein, atomically dispersed Pb single atoms on polydopamine (PDA‐Pb) are demonstrated, which display unprecedented catalytic activity toward the thermal decomposition of cyclotrimethylenetrinitramine (RDX). Impressively, RDX‐based propellants with the addition of PDA‐Pb catalyst exhibit substantially enhanced burning rates (14.98 mm s−1 at 2 MPa), which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…[ 32,33 ] Meanwhile, the Post‐TM, such as bismuth (Bi), lead (Pb), and tin (Sn), have been reported to show high electroactivity to the CO 2 reduction reactions (CO 2 RR). [ 34–38 ] Based on these works, the Bi‐ and Pb‐ SACs may also have great potential in electrocatalysis. Recently, Li's group has reported a novel SAC constructed by Bi atoms on N‐doped carbon networks (Bi SAs/NC) with hierarchical porosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 32,33 ] Meanwhile, the Post‐TM, such as bismuth (Bi), lead (Pb), and tin (Sn), have been reported to show high electroactivity to the CO 2 reduction reactions (CO 2 RR). [ 34–38 ] Based on these works, the Bi‐ and Pb‐ SACs may also have great potential in electrocatalysis. Recently, Li's group has reported a novel SAC constructed by Bi atoms on N‐doped carbon networks (Bi SAs/NC) with hierarchical porosity.…”
Section: Introductionmentioning
confidence: 99%
“…The latest study confirmed that the Pb‐SACs can be applied in boosting the combustion of energetic fillers in solid rocket propellants. [ 35 ] Xie et al also reported the atomically dispersed Sn δ + sites in N‐doped graphene have reached the robust and efficient CO 2 RR as well. [ 38 ] Moreover, although the alkali and alkaline earth metals are not usually applied as electrocatalysts, they have been commonly used as catalysts in thermocatalysis for organic reactions, supporting their intrinsic catalytic feature.…”
Section: Introductionmentioning
confidence: 99%
“…Single‐atom catalysts [ 17–19 ] (SACs), possessed features of single active site and maximum atom utilization efficiency, have attracted considerable research interests in oxidation reaction, [ 20,21 ] hydrogenation reaction, [ 22 ] electrocatalytic reaction, [ 23,24 ] and so on. For instant, Tao Zhang group used Pt SACs anchored on Fe 2 O 3 to improve hydrogenation activity of 3‐nitrostyrene with a high level of chemoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] What needs to be explained here is that a high nitrogen content not only leads to high energetic performance but also means a large amount of nitrogen gas rather than residual carbon in the combustion products of EMOFs, which is consistent with the demand for green and sustainable chemistry. On the other hand, although Pb-containing compounds, including Pb-MOFs, are the most widely-used combustion promoters in propellants, [32][33][34][35][36] the toxic nature of Pb makes them very harmful to the environment. As a consequence, there are more and more attempts to synthesize Pb-free and nitrogen-rich EMOFs in order to answer the call for sustainable development.…”
Section: Introductionmentioning
confidence: 99%